Lupus in fabula - Kőrizs, Imre (Studia Litteraria, 2015)
This paper seeks to list some pieces of evidence for the fact that the ancient Roman saying ‘lupus in fabula’ does not refer to a certain situation in a – lost, nursery, Aesopian, folk etc. – tale but it can be merely and directly traced back to a Greek and Roman belief that if a wolf saw somebody before the person saw the wolf, the sight of the wolf struck the person dumb. The wolf ‘in fabula’ is equivalent with the wolf ‘in situ’, namely the wolf ‘in a forest’, and they share an important feature: if one sees them, they strike one dumb. So, in this saying ‘fabula’ (talk, chat) there is a meta-forest. Then the paper, making use of this idea, offers an interpretation of Verg. ecl. 9, 54.